Second Cancers in a Patient with Gastric MALT Lymphoma - Lucy Navsaria; Alfonso Badillo; Michael Wang (Case Reports in Medicine)
Mucosa-associated lymphoid tissue (MALT) lymphoma is an extranodal low-grade B-cell lymphoma, which is thought to arise from a background of chronic immune stimulation, bacterial, viral, or autoimmune stimuli. Treatment advances have increased the number of MALT lymphoma survivors, but there is still debate as to whether these patients are at a higher risk of developing second cancers. This is a case of a long-surviving (>20 years) patient with multiple diagnosed malignancies following MALT lymphoma. We describe how modern oncological treatment plans can provide patients with prolonged survival and increased quality of life despite increasing age and multiple malignancies.